2023
DOI: 10.15586/aei.v51i1.689
|View full text |Cite
|
Sign up to set email alerts
|

Decursin alleviates LPS-induced lung epithelial cell injury by inhibiting NF-κB pathway activation

Abstract: Objective: To reveal the possible effects of decursin on viability, oxidative stress, and inflam-matory response in lipopolysaccharide (LPS)-treated human bronchial epithelial cells-2B (BEAS-2B) and human pulmonary artery endothelial cells (HPAEC) cells, and revealed the potential mechanisms. Methods: LPS was used to induce acute lung injury (ALI) in normal human lung epithelial cells, including BEAS-2B and HPAEC cells. Cell viability and apoptosis in response to LPS and decursin in BEAS-2B and HPAEC cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In contrast, castration-resistant prostate cancer, commonly named CRPC, is a type of prostate cancer that also proliferates at low levels of testosterone hormone (the primary sex hormone of male) (Sekhoacha et al, 2022). Castration is when the testicle gland (Khoobchandani et al, 2021;Pritam et al, 2021;Zhu & Dong, 2023).…”
Section: Modul Ation Of Immune Re Sp Onse Smentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, castration-resistant prostate cancer, commonly named CRPC, is a type of prostate cancer that also proliferates at low levels of testosterone hormone (the primary sex hormone of male) (Sekhoacha et al, 2022). Castration is when the testicle gland (Khoobchandani et al, 2021;Pritam et al, 2021;Zhu & Dong, 2023).…”
Section: Modul Ation Of Immune Re Sp Onse Smentioning
confidence: 99%
“…There was inhibition of angiogenesis near cancer cells, which resulted in cell death. In the end, the tumor growth stopped, and a reduction in tumor volume also occurred (Khoobchandani et al., 2021 ; Pritam et al., 2021 ; Zhu & Dong, 2023 ).…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a bioactive constituent of endotoxin, serves as the principal component of the cell wall in Gram-negative bacteria, and plays a pivotal role in eliciting inflammatory responses. 2 LPS can directly or indirectly initiate pathophysiological mechanisms within host cells. Consequently, LPS has emerged as the prevailing model for inducing inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether LTE can inhibit lung inflammation or other biological pathways to alleviate ALI through its active component Lut has not been fully covered. Furthermore, studies have shown that Decursin could mitigate LPS-evoked BEAS-2B and HPAEC cell injury via inactivating NF-κB pathway [ 15 ], and Chikusetsusaponin V could protect against LPS-stimulated ALI in mice by restraining NF-κB pathway activation [ 16 ]. However, whether the function of LTE in LPS-evoked ALI was concerned with NF-κB pathway remained unclear.…”
Section: Introductionmentioning
confidence: 99%